2012
DOI: 10.1007/s10711-012-9697-1
|View full text |Cite
|
Sign up to set email alerts
|

Berezin quantization of homogeneous bounded domains

Abstract: We prove that a homogeneous bounded domain admits a Berezin quantizatio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 27 publications
5
47
0
Order By: Relevance
“…Similar results were recently generalized by the first author and Mossa [34] to all bounded homogeneous (not necessarily symmetric) domains. The case of general homogeneous Kähler manifolds (not necessarily bounded domains) is still open.…”
Section: Balanced Metrics: the Compact And The Noncompact Casesupporting
confidence: 75%
“…Similar results were recently generalized by the first author and Mossa [34] to all bounded homogeneous (not necessarily symmetric) domains. The case of general homogeneous Kähler manifolds (not necessarily bounded domains) is still open.…”
Section: Balanced Metrics: the Compact And The Noncompact Casesupporting
confidence: 75%
“…For the case of non-compact manifolds, Loi-Mossa in [28] have shown that a bounded homogeneous domain admits a regular quantization. For the nonhomogeneous setting, we give the existence of regular quantizations on some Hartogs domains in [6] and [18].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Equation(20) extends to the noncompact setting the analogous equation proved in[4] for the compact case.…”
mentioning
confidence: 81%